Exploring the Behavioural Intention of Pet Owners Towards Pet Accessories: An Extended Theory of Planned Behaviour - Nor Azieda Shaikh Maidin; Muhamad Azrin Nazri; Nur Aqilah Hazirah Mohd Anim; Nor Asiah Omar (Faculty of Business and Accountancy, University of Selangor, 2025)
Indexed by MyCite